AUTUMN WHEAT TO FERTILITY PAST TENSE OF CROPS SOIL PRODUCTIVITY AND EFFECT - Бўриев Абдивахоб Абдираззақович (Web of Journals Publishing, 2024)
In order to maintain and increase soil fertility in areas vacated from winter wheat, intercropping with cotton, corn, mung bean, peas, and rapeseed was studied, and their effect on winter wheat yield was studied. As a result of planting these intercropping crops, including plants that have a positive effect on soil fertility, such as mung bean, peas, and rapeseed, it was observed that winter wheat yield indicators also changed in a positive direction.
Keywords: Companion crop, soil fertility, mung bean, chickpea, rapeseed, winter wheat, root and shoot residues, growing season, biological nitrogen, sideration, yield.